Homomorphisms of Approximation Spaces - Zhaohao Wang; Lan Shu; Xiuyong Ding (Journal of Applied Mathematics)
The notion of the homomorphism of approximation spaces is introduced. Some properties of homomorphism are investigated, and some characterizations of homomorphism are given. Furthermore, the notion of approximation subspace of approximation spaces is introduced. The relations between approximation subspaces and homomorphisms are studied.